Effects Of Three Acaricides On Plant Growth Parameters Of Garlic (Allium Sativum L.) (Asparagales: Amaryllidaceae) In Taskopru, Turkey - Cilbircioglu, Cihan; Cobanoglu, Sultan (Aperta, 2018)
In this study, we tested three acaricides (azadirachtin, abamectin, and hexythiazox) for their effects on developement parameters of garlic, Allium sativum L. (Asparagales: Amaryllidaceae). This research was done in 2013-2014 on one hectare of Taskopru garlic variety at Alatarla, Turkey. Each acaricide and the untreated control were tested four times on 16 plots. The effects of these acaricides on the germination rate and head weight of garlic was evaluated through regular sampling. Azadirachtin positively (129.00 +/- 2.74) affected germination of Taskopru garlic, while the other two acaracides had no effects on germination. None of the acaricides affected garlic head weights or head development. This is the first field study to evauate acaracides that may also affect plant development.
Keywords: 2. Zero hunger